Epipelon, phytoplankton and zooplankton responses to the experimental oligotrophication in a eutrophic shallow reservoir. (August 2020) - Amaral, Luyza Mayary; Carolina de Almeida Castilho, Maria; Henry, Raoul; Ferragut, Carla
Abstract: Epipelon can contribute to the maintenance of shallow lake oligotrophication. Herein, we simulated oligotrophication by diluting eutrophic water and evaluated epipelon biomass and structure and potential relationships with phytoplankton and zooplankton communities. Dilutions of 25–75% negatively impacted phytoplankton biomass and zooplankton diversity and increased Rotifera density. Additionally, the 25% dilution increased Copepoda density, but had no effect on Cladocera. On both experimental days, epipelon chlorophyll- a and algal density responded to oligotrophication, but the algal biomass response was less pronounced after 14 days. Ceratium furcoides was dominant in the phytoplankton, while diatom species were dominant in the epipelon. We observed that experimental oligotrophication can influence both the biomass and taxonomic structure of the algal and zooplankton communities. Overall, we concluded that experimental oligotrophication negatively impacted the phytoplankton biomass and favored the development of the phototrophic epipelon; however, a large reduction in eutrophication (>50%) is required for a significant algal response in the benthic environment of a shallow tropical reservoir. Graphical abstract: Image 1 Highlights: Epipelon was sensitive to small fluctuations in the light and nutrient availability. Epipelon responded the high oligotrophication, increasing epipelic motile diatom biomass. Phytoplankton biomass reduced with dilution, but the invasive Ceratium furcoides was dominant. Zooplankton responded to oligotrophication, but it exerted weak grazing pressure. Oligotrophication impacted the biomass and community structure of algae and zooplankton. Abstract : Epipelon can represent a potentially valuable tool for oligotrophication maintenance in shallow tropical lakes and reservoirs.